Sport-seasonal changes in body composition, growth, power and strength of adolescent wrestlers - Roemmich, J. N.; Sinning, W. E. (International Journal of Sports Medicine, 1996)
Changes in body composition, somatic growth, power and strength of high school wrestlers (W, n = 8, 15.9 +/- 0.3 yrs) and controls (C, n = 6, 16.1 +/- 0.2 yrs) were studied early, mid-, late-, and 3.5-months post-season. Elbow flexion peak power (FPP), peak torque (FPT), extension peak power (EPP), and peak torque (EPT) were measured on an isokinetic dynamometer. C demonstrated normal rates of somatic growth and gains in strength and power. However, for W, significant (p < 0.05) decreases were found in: weight (WT, 61.6 +/- 2.8 to 59.2 +/- 2.8 kg), relative fat (%BF) (7.8 +/- 0.7 to 6.1 +/- 0.7 %), FPT (33.3 +/- 2.3 to 29.9 +/- 2.7 Nm), FPP (125.8 +/- 0.3 to 107.8 +/- 8.4 W), EPT (37.5 +/- 2.5 to 36.2 +/- 3.8 Nm), and EPP (132.7 +/- 8.4 to 126.7 +/- 12.3 W), between early-season and late-season and significant increases in WT (5.4 +/- 0.4 kg), fat-free mass (FFM, 4.4 +/- 0.7 kg), FPT (9.4 +/- 1.7 Nm), FPP (38.8 +/- 8.8 W), EPT (6.5 +/- 1.0 Nm), and EPP (24.4 +/- 4.7 W), between late-season and post-season. Compared to C, W had significantly (p < 0.05) smaller increases in mid-arm girth and flexed mid-arm cross-sectional muscle area (X-SECT) during the wrestling season and larger increases in shoulder girth, abdominal girth, and mid-arm girth, X-SECT, and biacromial, biilium, and anterior-posterior chest breadths during the post-season. Power and strength measures were significantly correlated with FFM, lean upper limb volume (ULV), and X-SECT (r = 0.74 to 0.93, p <0.0001). When covaried for FFM, ULV or X-SECT seasonal declines in strength and power were no longer significant while post-seasonal increases remained. In conclusion, pre- to late- season W demonstrated a lack of lean tissue accretion and reductions in strength. At post-season these variables returned to, or were above, pre-season levels. Results of analysis of covariance indicated that lean tissue changes were associated with the changes in strength and power.